O compromisso de ajustamento de conduta como mecanismo de resolução de conflitos ambientais - Rocha, Géber Mafra (2007)
The constitutional bedding is the main landmark of the legal foundation of the sovereign State. Without this foundation, the structure of a country will be disfigured, and without base, all governmental action will leave the society to the abandonment of solutions and at the mercy of its endless conflicts. These are typical of the communitarian life and need alternatives so they can be equated in order to allow so longed for social peace. Therefore, the Constitution of the Federative Republic of Brazil, promulgated the 05 of October of 1.988, brought the possibility of application of characteristics rules to the conflict resolution, specially in environmental issues, giving clear definition to the previous mechanisms that have been received. This retrospection can be inferred from reading Chapter 1. The Commitment of Behavior Adjustment, that way called by legislation, as the conflict resolution mechanism, extraprocedural or procedural way - this one having as surrounding the public civil action -, appears, therefore, in 1.990, as a viable alternative for the composition of illegal situations in environmental issues amongst other subjects, matter dealt with more attention in Chapter 2. The highlight of Chapter 3 is the debate around what the Adjustment can represent to the law. The discussion about the legal nature of this institute is, probably, the more debated point by the brazilian commentators, specially as a legal deal, as defended by one and inconceivable for another part of the national doctrine. The mainstream admits the institute as being a transaction form. The making of and the effects of the Commitment of Behavior Adjustment are explained in Chapter 4, emphasizing legitimated subjects and the consequences in the legal world of the celebrated Term. Finally, a finalistic boarding on the institute is made, I order to clarify its real teleological content, boarded issue at this work, but specially in Chapter 5. Key words: Commitment of behavior adjustment, adjustment of behavior, term of behavior adjustment, public civil action, transaction, agreement, adjustment, diffuse rights.